PREDIKSI KEBANGKRUTAN DENGAN MODEL ALTMAN Z-SCORE PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - MARDIAH KENAMON; YETTY DWI WINAWUNG; HANINUN HANINUN (Universitas Bandar Lampung (UBL), 2018)
The purpose of this research is to determine the potential for bankruptcy in pharmaceutical companies listed on the Indonesia Stock Exchange. The data used are financial statements of pharmaceutical companies listed in Indonesia Stock Exchange 2012-2016 period. The analytical method used in this research is bankruptcy analysis with Altman Z-Score model. The results of this study explain that: (1) Based on the results of bankruptcy prediction analysis with Altman Z-Score model in pharmaceutical companies there are 2 (two) companies located in vulnerable areas / gray area bankrupt that is PT. Indofarma Tbk and PT. Pyridam Farma Tbk. (2) There are 5 (five) companies that do not go bankrupt namely PT. Darya-Varia Laboratoria Tbk, PT. Kimia Farma (Persero) Tbk, PT. Kalbe Farma Tbk, PT Merck Tbk, and PT. Taisho Pharmaceutical Indonesia Tbk.Keyword : Altman Z-Score, Bankruptcy Analysis Method